2021
DOI: 10.2340/00015555-3884
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcome Measures in Dermatology: A Systematic Review

Abstract: This is the first study to systematically evaluate all published dermatology-specific (for use across skin conditions), patient-reported outcome measures against the goldstandard Consensus-based Standards for the selection of health Measurement Instruments (COSMIN) criteria and make evidence-based recommendations for their use. The study found that no dermatology-specific patient-reported outcome measure can be unequivocally recommended for use. These results question the validity of the data collected using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…However, the increase in number of patients with a green/yellow outcome who still feels it is necessary to see a doctor indicates that we, with the PSO PROM are not able to measure the patient’s individual needs in regard to consultations. It is difficult to comprehensively assess the impact of living with a skin condition and Pattinson [ 16 ] describes that no single set of PROMs fully captured the patient experience.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increase in number of patients with a green/yellow outcome who still feels it is necessary to see a doctor indicates that we, with the PSO PROM are not able to measure the patient’s individual needs in regard to consultations. It is difficult to comprehensively assess the impact of living with a skin condition and Pattinson [ 16 ] describes that no single set of PROMs fully captured the patient experience.…”
Section: Discussionmentioning
confidence: 99%
“…(9) To be useful, PROMs must be well-validated, have favorable measurement properties across a broad spectrum of patients and disease severities, and offer interpretable and actionable data. (9)(10)(11)(12) Construct validity, or the evaluation of how well designed a measure is to evaluate its target area, HRQL, is vital to this goal. While the Dermatology Life Quality Index (DLQI) and the adapted DLQI-Relevant (DLQI-R) instruments have been evaluated in psoriasis, (13)(14)(15)(16)) construct validity testing for Skindex-16 remains sparse in psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical model of the impact of dermatological conditions. et al "Development of a conceptual framework for the Patient-Reported Impact of Dermatological Diseases measure" Acta Derm Venereol 2022Implications for Patient-Reported Impact of Dermatological Diseases (PRIDD)Multiple aspects of impact have not previously been captured using a single measurement instrument, and previous measures have focused on point-in-time impacts(3). This study supports the concepts of Cumulative Life Course Impairment(15) and the Major Life-Changing Decision Profile(16) in dermatology by unifying distinct point-in-time and cumulative impacts to attain a comprehensive understanding of the overall impact of living with a dermatological condition.…”
mentioning
confidence: 99%
“…Our earlier systematic review ( 3 ) of dermatologyspecific PROMs (which are used across dermatological conditions) revealed that the existing measures, including the widely-used Dermatology Life Quality Index (DLQI) and Skindex, could not be recommended for use according to the gold-standard consensus-based standards for the selection of health measurement instruments (COSMIN) criteria ( 4 ), primarily due to insufficient patient input during development. Thus existing PROMs may not fully capture aspects of impact that are important to patients.…”
mentioning
confidence: 99%